2006
DOI: 10.1002/uog.3866
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional sonographic determination of normal fetal mandibular and maxillary size during the second half of pregnancy

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 19 publications
3
37
0
1
Order By: Relevance
“…1,4,5 The addition of the frontomaxillary angle, maxillary and mandibular bone lengths, prefrontal diameter, and 3D ultrasonographic retronasal triangle, emphasizing the evaluation of the nasal bones, are other feasible soft markers for an early diagnosis of chromosomal abnormalities. 2,6,7 Therefore, further studies with a larger number of cases and longer range of gestational age to confirm the results we have presented and establish an accurate reference range for the Taiwanese population are warranted. …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…1,4,5 The addition of the frontomaxillary angle, maxillary and mandibular bone lengths, prefrontal diameter, and 3D ultrasonographic retronasal triangle, emphasizing the evaluation of the nasal bones, are other feasible soft markers for an early diagnosis of chromosomal abnormalities. 2,6,7 Therefore, further studies with a larger number of cases and longer range of gestational age to confirm the results we have presented and establish an accurate reference range for the Taiwanese population are warranted. …”
Section: Discussionsupporting
confidence: 75%
“…2,6 Many studies recommend the measurement of the frontomaxillary facial angle and the mandibulomaxillary facial angle for first-trimester screening of fetuses with chromosomal defects. 3,7,8 The purpose of our study was to establish the additional ultrasonographic markers for first-trimester fetal screening. We measured the maxillary and mandibular angles of singleton fetuses among Taiwanese pregnant women at 11 þ0 e13 þ6 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…In 6/24 fetuses with CL-CLP, the MR study revealed abnormalities in the following parameters with respect to normal development of the fetal face: IFA, FMA, IOD. We considered normal the fetuses with these parameters in the normal range, as defi ned by the 2D/3D US study and reported in the literature [12,19,20].…”
Section: Resultsmentioning
confidence: 99%
“…However, prenatal screening for major skeletal anomalies in the jaw area continues to be dominated by subjective standards. While the jaw lengths (including the bimaxillary length ratio) are potentially capable of revealing anomalies of this type [5,11,39,50], objective ways to assess these parameters in fetuses were proposed but have not become established.…”
Section: Introductionmentioning
confidence: 99%
“…Die pränatale Diagnostik ausgeprägter skelettaler Dysgnathien erfolgt jedoch immer noch überwiegend subjektiv. Obwohl die Betrachtung der Ober-und Unterkieferlänge sowie das Verhält-nis zueinander das Potenzial hätten, diese zu erkennen [5,11,39,50], sind bisher beschriebene objektive Verfahren zur Bestimmung der Längen fetaler Ober-und Unterkiefer in der Routinediagnostik nicht etabliert.…”
Section: Introductionunclassified